Artemether/Lumefantrine for the Treatment of P. malariae in a Patient on Hemodialysis - Rita Patrocínio-Jesus; João Cunha; Diva Trigo; Bárbara Flor-de-Lima; Patrícia Pacheco (Case Reports in Medicine)
The combination of artemether/lumefantrine is indicated for the treatment of acute uncomplicated Plasmodium falciparum malaria. There have been no clinical trials to assess the efficacy of this medication in patients with renal impairment. While it is unlikely that artemether/lumefantrine would be removed during dialysis, clinical experience regarding drug use in this setting is limited. In this article, the authors report successful treatment of Plasmodium malariae malaria on a patient with end-stage kidney disease undergoing hemodialysis.